"Authentic" Queer Identities – Koos Prinsloo as a Site of Contestation. Issue 1 (2nd January 2019) - Kumalo, Siseko H.
Summary: Koos Prinsloo's short story, "Promise you'll tell no-one", highlights three aspects that continue to plague Afrikaner identity. The first of these are the phallus, understood here as the symbol of patriarchal power which was the epicentre of Afrikaner identity under the apartheid regime in South Africa, governing both the home and politics. The second aspect is the vacillation between "homomasculinity" (Sonnekus 2013: 35) and heterosexuality, with Afrikaner male identity defined as oppositional to homo-masculinity/homosexuality – with the latter categories typifying the Other . Lastly, Prinsloo deals with race, albeit in a fleeting manner. His use of race in "Promise you'll tell no-one" reveals the nature of the dogmatic racial categories of apartheid during the 1980s in South Africa. Dealing with each of these aspects in seriatim, as a way of raising the question of an authentic "queer voice", I highlight how Prinsloo attempts to step outside the strictures of Afrikaner identity. My analysis reveals, however, that while his attempt may be genuine, Prinsloo cannot escape the place-identity into which he was born and from which he wrote. To explicate this position, I refer to other texts such as Oliver Hermanus's Skoonheid (2011), Mark Behr's (1996) The Smell of Apples ( Die reuk van appels) and John Trengrove's Inxeba (2013). I conclude the article by reposing the question in the context of contemporary South African society so as to glean insights from this short story as a way of better understanding questions of justice as they relate to queerness.